2014
DOI: 10.4238/2014.january.24.2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of methylenetetrahydrofolate reductase polymorphisms and folate intake on the risk of gastric cancer and their association with Helicobacter pylori infection and tumor site

Abstract: ABSTRACT. Folic acid and methylenetetrahydrofolate reductase (MTHFR) may both affect the development of human cancer. We conducted a population-based case-control study in a Chinese population to investigate the potential role of folate intake and MTHFR gene polymorphisms in gastric cancer, and their interaction with infection by Helicobacter pylori and tumor location. A total of 767 patients with newly diagnosed gastric cancer and 775 controls were selected for this study. Genotyping of MTHFR C677T and A1298C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Our null results are consistent with previous epidemiologic studies in the Korean population . A few studies have investigated the interaction between MTHFR polymorphisms and folate intake on gastric cancer risk, but these results are also inconsistent . We found a statistically significant interaction between dietary folate intake and MTHFR G1793A, which was not previously reported.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our null results are consistent with previous epidemiologic studies in the Korean population . A few studies have investigated the interaction between MTHFR polymorphisms and folate intake on gastric cancer risk, but these results are also inconsistent . We found a statistically significant interaction between dietary folate intake and MTHFR G1793A, which was not previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…Two common polymorphisms of MTHFR , C677T, and A1298T, reduce enzyme activity and lead to lower levels of 5‐methyl‐THF and the accumulation of 5,10‐methylene‐THF . Several studies have reported that the TT genotype of MTHFR C677T is associated with an increased gastric cancer risk , whereas other studies have shown a negative association or null results . Most studies investigating the effect of MTHFR A1298T have reported a null association with gastric cancer risk , but Vollset et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity analysis of individual studies by sequential removal and the control population—results were deviated from the HWE. 23 , 33 , 34 , 37 , 41 , 42 , 46 All the significance of OR did not exclude the changes after these studies, and our results were robust and reliable. Potential bias was examined by Begg's funnel plot and Egg's test.…”
Section: Resultsmentioning
confidence: 61%